Intrahepatic biliary cystadenoma: Confusion, experience, and lessons learned from our center - Yang, Yongguang; Chen, Weihuang; Cen, Haiqiang; Li, Zuobiao; Di, Xiaoqing; Wu, Yongjun; Liu, Lijuan (Frontiers in Oncology, 2022)
Background Intrahepatic biliary cystadenoma (IBC) is a rare benign cystic tumor of the liver. So far, it has not been comprehensively understood, which causes incorrect diagnosis, treatment confusion, and even inappropriate treatment. Here, we reviewed clinical data of IBC patients in our center, shared our experiences and lessons learned, and improved the level of diagnosis and treatment. Methods The clinical data of 10 patients with pathologically diagnosed IBC, admitted to the Department of Hepatobiliary Surgery of the Affiliated Hospital of Guangdong Medical University from January, 2007, to January, 2022 were retrospectively analyzed. Results 10 patients underwent surgery and were discharged successfully. Cyst morphology: multiple cysts: 6 cases (6/10), monocular cyst: four cases(4/10). Six patients (6/10) were diagnosed as IBC preoperatively and received hepatectomy. Four patients with monocular cyst IBC underwent intraoperative frozen section examination, except one case showed IBC; the rest were misdiagnosed as simple liver cyst. In three misdiagnosed patients, one underwent open left hepatectomy seven days after the initial operation. The other patient refused to undergo reoperation and required follow-up observation. The last patient could not tolerate hepatectomy due to insufficient residual liver volume and chose follow-up observation Conclusion For IBC, especially monocular IBC, it is easy to be misdiagnosed as simple hepatic cyst, which brings great confusion to clinical treatment. We propose strengthening communication with pathologists to deepen understanding of IBC. Attention should be paid to the cyst wall’s shape and the cyst fluid’s properties during the operation to avoid the missed diagnosis, misdiagnosis, or even improper operation. For suspicious cases, directly choose hepatectomy to avoid reoperation after thoroughly evaluating the patient’s condition.